Endothelialization of an ePTFE vessel prosthesis modified with an antithrombogenic fibrin/heparin coating enriched with bound growth factors - Táborská, Johanka; Riedelová, Zuzana; Brynda, Eduard; Májek, Pavel; Riedel, Tomáš (RSC advances, 2021)
Early and late thrombosis remain the most frequent reasons for the failure of synthetic cardiovascular grafts. Long-term hemocompatibility of implanted synthetic grafts can be achieved if a natural living endothelium is formed over its blood-contacting surface. Here we present a modification of a standard expanded polytetrafluorethylene (ePTFE) vessel prosthesis by a controlled preparation of a fibrin mesh enriched with covalently bound heparin and noncovalently bound vascular endothelial growth factor (VEGF) and fibroblast growth factor (FGF). Compared to a bare prosthesis, the coated prosthesis showed excellent antithrombogenic properties after contact with heparinized fresh human blood. Human umbilical vein endothelial cells seeded on the inner surface of the coated prosthesis formed a confluent layer in 5 days, whereas only small colonies of cells were scattered on the bare prosthesis. Viability of the cells was promoted mainly by FGF immobilized on the coating. These findings suggest that the coating may prevent acute thrombus formation and support the self-endothelialization of an implanted ePTFE vascular graft in vivo.